Transcriptomic Profiling Reveals the Involvement of the Phenylpropanoid–Lignin Pathway in the Response of Maize Roots to Zinc Stress - Ying Zhou; Tianyu Gu; Yan Gao; Jingtao Qu; Hongjian Zheng; Yuan Guan; Jiashi Peng (Plants)
Zinc (Zn) is an essential micronutrient required for plants to perform various metabolic functions, and plant responses to Zn deficiency have been extensively studied. However, excessive levels of Zn in soil can induce toxic effects in plants, posing a substantial challenge to global agricultural productivity. Consequently, elucidating the response mechanisms of crop plants to excessive Zn toxicity is currently of great significance. In this study, seedlings of maize inbred line B73 were exposed to excessive Zn treatment, and transcriptomic profiling of the roots was conducted at 0, 2, 6, 12, 24, and 48 h post-treatment. In addition to changes in the expression of genes encoding zinc-regulated, iron-regulated transporter-like protein (ZIP), metal tolerance protein (MTP), and yellow stripe-like (YSL) transporter family members involved in Zn transport, we observed that differentially expressed genes (DEGs) were significantly enriched in the phenylpropanoid–lignin metabolic pathway across all treatment stages, including the early (2 and 6 h), middle (12 and 24 h), and late (48 h) stages of Zn treatment. Among the 11 core structural enzyme-encoding genes involved in monolignols biosynthesis from phenylalanine in this pathway, the expression of eight of them was altered by Zn treatment. Additionally, genes encoding peroxidase (POD), which are responsible for the polymerization of monolignols into lignin, demonstrated extensive changes across all treatment stages, particularly at the late stage. The expression levels of these key enzyme genes were further validated using quantitative real-time PCR. Correspondingly, the activity of POD enzymes and the lignin content both significantly increased in Zn treated roots. These findings suggest that the phenylpropanoid–lignin metabolic pathway plays a crucial role in maize root responses to excessive Zn stress.